Data-driven magnetohydrodynamic modelling of a flux-emerging active region leading to solar eruption - Chaowei Jiang (Nature Portfolio, 2016)
Solar eruptions heavily influence space weather, but what are their causes remains an open question. Here the authors present a magnetohydrodynamic model of a solar eruption directly driven by solar magnetograms, following the transition from pre-eruptive to eruptive state.